Effects of rs3802177 G/A polymorphism on SLC30A8 mRNA and hsa-miR-183-5p in Malay women with gestational diabetes mellitus - Sajad Jamalpour; Phang Kean Chang; Reza Vazifehmand; HESAM, KAMYAB; Siti Zawiah Omar; Shamsul Mohd Zain (Springer Science and Business Media LLC, 2025)
Gestational diabetes mellitus (GDM) is characterized by the initial presentation of impaired glucose tolerance identified during pregnancy. Numerous investigations have explored the associations between single nucleotide polymorphisms (SNPs) and microRNAs in relation to the susceptibility to GDM across diverse populations. This study aimed to investigate the interplay among rs3802177 G/A 3′ UTR polymorphism, SLC30A8 mRNA expression, and hsa-miR-183-5p in Malay women with GDM. TargetScanHuman, miRBase, miRRecord, and Sfold bioinformatics tools were applied to predict and select a putative microRNA that has a significant interaction with SLC30A8 mRNA at the 3′ UTR region. DNA was extracted and genotyped using the Sequenom Mass ARRAY method. Quantitative PCR was performed to evaluate SLC30A8 mRNA and hsa-miR-183-5p expression levels. Preliminary bioinformatics analysis revealed that hsa-miR-183-5p is a potential target for SLC30A8. Thermodynamic evaluation confirmed a negative association between polymorphisms and SLC30A8 mRNA secondary structure (P = 0.8027). Data analysis showed that the GG genotype in patients with GDM is a risk allele for GDM in the Malay population. Furthermore, the SLC30A8 gene was significantly downregulated (P < 0.05), whereas miR-183-5P was significantly upregulated (P < 0.05) in patients with the GG genotype. In addition, the ROC curve analysis revealed that hsa-miR-183-5p has potential as a biomarker (AUC = 0.7926 ± 0.02045, p = 0.0001) in the first trimester of GDM. In conclusion, this study provides the first evidence of a substantial association in the interplay among the rs3802177 G/A SNP, SLC30A8 mRNA expression, and hsa-miR-183-5p expression levels in the Malay population.
Keywords: Gestational diabetes mellitus; Hsa-miR-183-5p; Malaysia; Rs3802177 G/A; SLC30A8